MORPHOMETRICAL CHANGES OF THE HEPATOCYTES UNDER INFLUENCE OF THE PESTICIDE 2,4-D AND AFTER INTRAGASTRIC CORRECTION BY GLUTARGIN - Кулинич, Г. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the experiment on 22 white rats we learned the influence of pesticide 2,4-D on structure of liver. The dystrophic changes of hepatocytes were observed. Positive effects on structure and morphometrical indexes (square of hepatocyte and its nucleus, index square hepatocyte/ square of its nucleus, coefficient of form of hepatocyte and its nucleus) of the liver by intragastrical introduction by Glutargin were observed during the rehabilitation period (since 60-th day).